2017
DOI: 10.1186/s12967-017-1161-4
|View full text |Cite
|
Sign up to set email alerts
|

Activin B is a novel biomarker for chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) diagnosis: a cross sectional study

Abstract: BackgroundInvestigations of activin family proteins as serum biomarkers for chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME). CFS/ME is a disease with complex, wide-ranging symptoms, featuring persistent fatigue of 6 months or longer, particularly post exertion. No definitive biomarkers are available.MethodsA cross-sectional, observational study of CFS/ME patients fulfilling the 2003 Canadian Consensus Criteria, in parallel with healthy non-fatigued controls, was conducted. Comparisons with a previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 34 publications
5
46
1
2
Order By: Relevance
“…From among a broad range of pathology test and cytokine assay results (Additional file 1: Table S2), only serum activin B was significantly different (p < 0.05) for the direct comparison between ME/CFS and study control (healthy) participants, as previously reported [24]. Individual participant serum and urine pathology results generally fell within the laboratory reference interval.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…From among a broad range of pathology test and cytokine assay results (Additional file 1: Table S2), only serum activin B was significantly different (p < 0.05) for the direct comparison between ME/CFS and study control (healthy) participants, as previously reported [24]. Individual participant serum and urine pathology results generally fell within the laboratory reference interval.…”
Section: Resultssupporting
confidence: 66%
“…IL-10 has been implicated in the pathogenesis of ME/CFS [37, 38], but there is no evidence from this study for a relationship between IL-10 levels and presence/severity of ME/CFS symptoms. On the other hand, Activin B has been recently identified as significant when separating this ME/CFS cohort from the same study (healthy) controls, [24] a relationship that was also reflected by WST analysis.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Accordingly, molecular biomarkers have been pursued across multiple areas of research. For example, the role of the immune system in ME/CFS has been studied for decades, raising cytokines as potential biomarkers of disease [8][9][10][11][12][13][14] whose clinical utility would be aided by their accessibility in blood. Other cytokine studies have utilised cerebrospinal fluid [15,16], the acquisition of which is more invasive than drawing blood, and so could be less amenable to a routine diagnostic test.…”
Section: Introductionmentioning
confidence: 99%
“…The ideal molecular biomarkers would be straightforward to sample and assess, and they also exhibit high sensitivity and specificity. For these reasons, the search for biomarkers has extended to investigating the utility of routine blood pathology tests, but the results are either inconsistent [9,10] or require further study [30]. The recent development of a nanoneedle bioarray to measure the electrical impedance of ME/CFS peripheral blood mononuclear cells (PBMCs) in plasma is highly promising, but requires identification of the underlying mechanism and proven specificity for ME/CFS [31].…”
Section: Introductionmentioning
confidence: 99%